Analisis Pengaruh Leverage dan Growth Opportunity terhadap Cash Holding - Annisa, Mutiara Lusiana; Kertarajasa, Astro Yudha (Jurnal Serambi Ekonomi dan Bisnis, 2024)
The aim of the research is to analyze the effect of leverage and growth opportunity on cash holding. The population in the research are manufacturing companies listed on the Indonesian Stock Exchange (BEI) for the 2021-2022 period which operate in the advertising, printing and media sectors. The type of sampling used in this research is purposive sampling. The companies that were the objects of research were 16 companies over 2 periods (2021-2022), namely Mahaka Media Tbk, Elang Mahkota Teknologi Tbk, MD Pictures Tbk, Fortune Indonesia Tbk, Jasundo Tiga Perkasa Tbk, First Media Tbk, Link Net Tbk, Star Pacific Tbk, Mahaka Radio Integra Tbk, Intermedia Capital Tbk, Media Nusantara Citra Tbk, MNC Studios International Tbk, MNC Sky Vision Tbk, Surta Citra Media Tbk, Tempo Inti Media Tbk, and Visi Media Asia Tbk. The research results show simultaneously that leverage and Growth Opportunity have a significant effect on Cash Holding. Leverage shows a negative influence on Cash Holding and Growth Opportunity also shows a negative influence on Cash Holding. In accordance with the pecking order theory, cash decreases due to debt. High leverage can mean that the company has a high dependence on external loans to finance its assets. Meanwhile, Growth Opportunity has a significant negative effect on Cash Holding. Companies with large growth opportunities tend to have low cash holdings policies. This is because the company will attract the attention of investors through growth opportunities for investment. Growth opportunities require a large amount of funds so that they drain existing cash, according to the theory that growth opportunities cause the company's cash holding level to be low.